Water Disinfection Studies using Hybrid Process of Photocatalysis and Photo-Fenton in Fixed Mode - Ina, Thakur (My University, 2022)
Contamination of water resources by pathogenic bacteria and associated diseases is a major source of concern for water quality worldwide. Contamination by pathogens is a severe problem that affects all kinds of water bodies, making its identification and understanding important. Advanced oxidation processes (AOPs) such as photo-Fenton and TiO2 photocatalysis have achieved promising applications for the disinfection of wastewater. Yet, both of them have a few limitations such as prolonged treatment time, catalyst separation, electron-hole recombination, iron sludge formation, and higher H2O2 dose which have hindered their effective implementation at the field scale. Therefore, considerable attention has been paid in the present work to explore the practical applications of AOPs by resolving almost all of the issues raised by these individual processes (photocatalysis or photo-Fenton). Attempts were made to combine these two processes within the same treatment unit for the increased disinfection of targeted bacteria, i.e., E. coli. This hybrid technique effectively covers the shortcomings of both technologies ( photocatalysis + photo-Fenton) due to the presence of a higher amount of OHo . To execute the hybrid process, a low-cost and visibly active Fe−TiO2 composite was fabricated using industrial waste materials such as foundry sand (FS) and fly ash (FA) (iron source) mixed with clay in the ratio of 2:1:1. A thin film of TiO2 was coated on spherical composite beads leading to photocatalysis and iron leaching from the composite, leading to photo-Fenton thus incorporating a hybrid effect in one system. For the lab-scale trials inactivation of E. coli was carried out under artificial UV light. Operating parameters such as UV light intensity, size of beads, the addition of oxidant, change in pH, and area/volume ratio of the reactor was optimized for the inactivation of E. coli. In the hybrid process, 6.2 E. coli log reduction was observed in 90 min of reaction time. An increase of 26 % of synergy with the hybrid process was obtained in comparison to photocatalysis and photo-Fenton alone. The kinetic parameters such as k of log-linear and δ of double Weibull for fitting the E. coli inactivation results were used for comparing the different techniques and found that the hybrid-technique in fixed mode (k = 0.16 min-1 , δ1 = 8.63 min, δ2 = 27.7 min) proved to be significantly faster in comparison to other techniques; TiO2 assisted photocatalysis (k = 0.6 min-1 ; δ1 = 23.1 min, δ2 = 76 min); photo-Fenton (k = 0.07 min-1 ; δ1 = 17.66 min, δ2 = 33.53 min; H2O2 with UV ( k = 0.04 min-1 ; δ1 = 34.05 min, δ2 vi = 100.95 min) and Only UV(k = 0.03 min-1 ; δ1 = 51.91 min, δ2 = 207.73 min). Thus the obtained results present a promising potential of the hybrid technology for the treatment of E. coli in water. The beads were proved to be durable for more than 50 recycles for the inactivation of E. coli. To confirm the presence of TiO2, morphological analysis and elemental composition for fresh as well as recycled composite beads were done using SEM and EDS respectively. The activity of the catalyst and the presence of Fe was also checked by using XRD, FTIR, and DRS analysis. To promote the applicability of AOPs at the field scale in near future, it is mandatory to execute the scale-up trails of lab-scale results. The established in-situ hybrid effect in the present study using composite beads was scaled up for the disinfection of E. coli with the development of pilot-scale reactors. The pilot-scale reactors taken into consideration for the present study were UV-assisted re-circulation type fixed-bed glass reactor and solar once through cascade reactor with a total working volume of 2 L and 6 L, respectively. The detailed cost of the process has been evaluated using each type of reactor. The first reactor that was studied is the continuous recirculating flatbed reactor. The performance of the hybrid process (Fe-TiO2) was evaluated in terms of reaction rate constant, and some other operating parameters. This hybrid process showed a significant increase in reaction rate constant (0.065 min-1 ) compared to photo-Fenton (0.029 min-1 ) and photocatalysis (0.025 min-1 ) in 150 min of treatment time. The P-value was less than 0.0001 and the F-value was greater than 5 for each process. Response surface methodology (RSM) with box Behnken design (BBD) has been employed for the optimization of different parameters. The optimized values of the operating parameters were found to be 3.5, 62 mg L 1 , 106 mL min-1 for the reaction pH, H2O2 concentration, and flow rate, respectively. With these optimum conditions, a percentage reduction of E. coli of 93% was observed. The synergistic effect of the hybrid process over photocatalysis was observed to be 61 % and over photo-Fenton was 55 %. The overall synergy of the hybrid process came out to be 17 %. Various characterizations (SEM−EDX, UV-DRS, FTIR, and XRD) confirmed the longevity and the stability of the Fe−TiO2 composite even after 50 cycles. The total cost of killing E. coli in the solution was US $0.16 per liter, showing the potential for commercial application. A pilot-scale fixed-bed continuous once-through reactor was used to study the inactivation of E. coli. The reactor approached the plug flow condition in 45 min of retention time (Ʈ) and a 100% inactivation of E. coli cells was observed with an H2O2 dose of 50 mg L−1 , 100% vii surface area covered, 6 L h−1 of flow rate, and three reactors in series. Furthermore, these Fe TiO2 composites showed exceptional durability even after 100 recycles which further claims the novelty of this technology. The total operating cost for treating water came out to be 0.00827 US$ for one reaction per cycle. No regrowth of bacterial cells in the solution even after 48 h of treatment, clearly indicated the commercial viability of the present reactor system. The cell wall damage was confirmed by the increase in the K+ concentration at regular intervals. Also, the total cost of the process assessed in this study is substantially lower than other AOPs-related studies found in the literature. Therefore, the current fixed-bed once-through reactor under sunlight integrating into situ hybrid effects with demonstrated validity of theoretical prediction might be efficiently used at a large scale to handle the wastewater in lesser time. Further, for the authentication of the results of the hybrid effect, the study has been extended to the real secondary treated municipal wastewater. The study was conducted in batch mode and then was implemented in continuous once-through mode. In the batch scale study, 100% inactivation of bacteria with optimized parameters such as 0.9 g L-1 of H2O2 dose, 5.5 pH, and 100 % surface area covered with the catalyst in 60 min of treatment time was observed. 54 % and 40% reduction in BOD and COD respectively was also observed in 60 min. The scale-up trials using the in-situ hybrid process for the treatment of actual municipal wastewater were executed in a pilot-scale solar once-through cascade reactor system and 4.5 log reduction of bacteria was observed in 45 min of treatment time. Recycling and reuse of the catalyst validated the economic feasibility of the process
Keywords: Disinfection; Composite; Dual Process; Waste materials